The NLRP3-Mediated Neuroinflammatory Responses to CdTe Quantum Dots and the Protection of ZnS Shell - Wu T (Dove Medical Press, 2020)
Tianshu Wu,1 Xue Liang,1 Keyu He,2 Xi Liu,1 Yimeng Li,1 Yutong Wang,1 Lu Kong,1 Meng Tang1 1Key Laboratory of Environmental Medicine and Engineering, Ministry of Education, School of Public Health, Southeast University, Nanjing 210009, People’s Republic of China; 2Blood Transfusion Department, Zhongda Hospital, Southeast University, Nanjing 210009, People’s Republic of ChinaCorrespondence: Tianshu Wu Email ninatswu@126.comIntroduction: Since CdTe quantum dots (QDs) are still widely considered as advanced fluorescent probes because of their far superior optical performance and fluorescence efficiency over non-cadmium QDs, it is important to find ways to control their toxicity.Methods: In this study, the adverse effects of two cadmium-containing QDs, ie, CdTe QDs and CdTe@ZnS QDs, on the nervous system of nematode C. elegans, the hippocampus of mice, and cultured microglia were measured in order to evaluate the neuroinflammation caused by cadmium-containing QDs and the potential mechanisms.Results: Firstly, we observed that cadmium-containing QD exposure-induced immune responses and neurobehavioral deficit in nematode C. elegans. In the mice treated with QDs, neuroinflammatory responses to QDs in the hippocampus, including microglial activation and IL-1ß release, occurred as well. When investigating the mechanisms of cadmium-containing QDs causing IL-1ß-mediated inflammation, the findings suggested that cadmium-containing QDs activated the NLRP3 inflammasome by causing excessive ROS generation, and resulted in IL-1ß release.Discussion: Even though the milder immune responses and neurotoxicity of CdTe@ZnS QDs compared with CdTe QDs indicated the protective role of ZnS coating, the inhibitions of NLRP3 expression and ROS production completely reduced the IL-1ß-mediated inflammation. This provided valuable information that inhibiting target molecules is an effective and efficient way to alleviate  the toxicity of cadmium-containing QDs, so it is important to evaluate QDs through a mechanism-based risk assessment.Keywords: quantum dot, Caenorhabditis elegans, hippocampus, BV2 cells, interleukin-1ß, NLRP3 inflammasome